Lymph node size and its association with nodal metastasis in ductal adenocarcinoma of the pancreas - Jaehoon Shin; Seungbeom Shin; Jae Hoon Lee; Ki Byung Song; Dae Wook Hwang; Hyoung Jung Kim; Jae Ho Byun; HyungJun Cho; Song Cheol Kim; Seung-Mo Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Although lymph node metastasis is a poor prognostic factor in patients with pancreatic ductal adenocarcinoma (PDAC), our understanding of lymph node size in association with PDAC is limited. Increased nodal size in preoperative imaging has been used to detect node metastasis. We evaluated whether lymph node size can be used as a surrogate preoperative marker of lymph node metastasis. Methods We assessed nodal size and compared it to the nodal metastatic status of 200 patients with surgically resected PDAC. The size of all lymph nodes and metastatic nodal foci were measured along the long and short axis, and the relationships between nodal size and metastatic status were compared at six cutoff points. Results A total of 4,525 lymph nodes were examined, 9.1% of which were metastatic. The mean size of the metastatic nodes (long axis, 6.9±5.0 mm; short axis, 4.3±3.1 mm) was significantly larger than that of the non-metastatic nodes (long axis, 5.0±4.0 mm; short axis, 3.0±2.0 mm; all p<.001). Using a 10 mm cutoff, the sensitivity, specificity, positive predictive value, overall accuracy, and area under curve was 24.8%, 88.0%, 17.1%, 82.3%, and 0.60 for the long axis and 7.0%, 99.0%, 40.3%, 90.6%, and 0.61 for the short axis, respectively. Conclusions The metastatic nodes are larger than the non-metastatic nodes in PDAC patients. However, the difference in nodal size was too small to be identified with preoperative imaging. The performance of preoperative radiologic imaging to predict lymph nodal metastasis was not good. Therefore, nodal size cannot be used a surrogate preoperative marker of lymph node metastasis.